1970
DOI: 10.1182/blood.v36.3.287.287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythropoietin on Proliferation of Erythroid Stem Cells in the Absence of Transplantable Colony-forming Units

Abstract: A single administration of Myleran eradicated colony-forming stem cells from marrow or spleen of mice for a period of two weeks or longer. Erythropoiesis was restored during that time, and the exclusion of cell influx from the colony-forming progenitors into the intermediary erythroid stem cell compartment permitted a study of the effects of erythropoietin on the kinetics of the latter. The results indicate that erythropoietin, in addition to its role in transforming immediate precursors into proerythroblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

1972
1972
1986
1986

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 15 publications
3
9
0
1
Order By: Relevance
“…Although BFU-e can form erythroid colonies in the absence of erythropoietin, both in vivo and in vitro studies indicate that they are responsive to it even at an early stage in their development. Thus, in mice treated with cytotoxic drugs which suppress both blood production and the self-renewal and differentiation of CFU-s, multiple in vivo injections of erythropoietin accelerated the recovery of erythropoiesis [22,49], suggesting that the hormone can recruit cells capable of differentiating in response to it [66]. In vitro studies by Dessypris and Krantz also demonstrated that erythropoietin is a mitogen for early marrow BFU-e, albeit in the presence of serum .…”
Section: Erythropoietin-responsive Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although BFU-e can form erythroid colonies in the absence of erythropoietin, both in vivo and in vitro studies indicate that they are responsive to it even at an early stage in their development. Thus, in mice treated with cytotoxic drugs which suppress both blood production and the self-renewal and differentiation of CFU-s, multiple in vivo injections of erythropoietin accelerated the recovery of erythropoiesis [22,49], suggesting that the hormone can recruit cells capable of differentiating in response to it [66]. In vitro studies by Dessypris and Krantz also demonstrated that erythropoietin is a mitogen for early marrow BFU-e, albeit in the presence of serum .…”
Section: Erythropoietin-responsive Cellsmentioning
confidence: 95%
“…This was not true for CFU-s and colony-forming units granulocytelmacrophage spivak 144 (CFU-gm), suggesting that CFU-s and CFU-e are separated by a number of cell divisions and do not share a direct precursor-progeny relationship [47]. CFU-s and CFUe also have different physical characteristics as demonstrated by sedimentation at unit gravity [48], and agents which suppress the proliferation of CFU-s do not prevent expansion of the erythroid progenitor cell pool by erythropoietin [49]. Taken together with the substantial evidence provided by Oguwu and colleagues for the stochastic behavior of pluripotent and multipotent stem cells [50], it is likely that the effects of erythropoietin are limited to specific types of committed progenitor cells not involved in self-renewal.…”
Section: Il3mentioning
confidence: 99%
“…In the present study, further information is presented on this regulation, and the question is examined whether a cytokinetic balance exists between the two processes stimulated by erythropoietin. As in our previous study (Reissmann & Samorapoompichit, 1970) Myleran was used to suppress in mice their CFU to such low levels that no significant inflow of CFU into the ERC compartment could take place. Polycythemic mice were employed and the erythropoietin test (Gurney, Lajtha & Oliver, 1962) was used to assess the ERC population present at various days after Myleran administration.…”
Section: Introductionmentioning
confidence: 93%
“…Emphasis has been placed on erythropoietin which promotes the differentiation of the erythropoietic stem cells to normoblasts [23] . Erythropoietin has been reported to stimulate vasoproliferation [24] and the production of stem cells [24,25] . Whether erythropoietin is the sole humoral factor or whether other humoral or local marrow factors are necessary for the marrow erythroid hyperplasia is unknown.…”
Section: At the Marrow Level Major Attention Has Been Paid To The Dismentioning
confidence: 99%